2000
DOI: 10.1046/j.1524-4725.2000.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Imiquimod 5% Cream for the Treatment of Superficial Basal Cell Carcinomas in a Basal Cell Nevus Syndrome Patient

Abstract: Imiquimod 5% cream appears to be effective in eradicating superficial nonfacial BCCs. The degree of local inflammatory response may affect the patients' tolerability of treatment and therefore patient compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
9

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 4 publications
1
77
0
9
Order By: Relevance
“…It usually occurs in regions of lower fur density and lesser pigmentation such as the nose, pinnae and periocular region (Rodaski and Werner, 2009). In mammals, the causes and pathogenetic mechanisms of the disease are very similar to others involved in actinic keratosis (Festa-Neto, 2002), a dysplasia of keratinocytes (Kagy and Amonette, 2000) that is usually a consequence of solar dermatitis (Festa-Neto, 2002;Grupta et al, 2002).…”
Section: Avaliaram-se a Viabilidade E A Eficácia Da Utilização Do Imimentioning
confidence: 88%
“…It usually occurs in regions of lower fur density and lesser pigmentation such as the nose, pinnae and periocular region (Rodaski and Werner, 2009). In mammals, the causes and pathogenetic mechanisms of the disease are very similar to others involved in actinic keratosis (Festa-Neto, 2002), a dysplasia of keratinocytes (Kagy and Amonette, 2000) that is usually a consequence of solar dermatitis (Festa-Neto, 2002;Grupta et al, 2002).…”
Section: Avaliaram-se a Viabilidade E A Eficácia Da Utilização Do Imimentioning
confidence: 88%
“…It has also been used successfully to treat patients with intraepidermal neoplasia including Bowen’s disease [25, 26, 27, 28, 29, 30, 31]. Several studies and case reports on the use of imiquimod in the treatment of multiple BCC indicate its effectiveness, especially in patients with multiple or difficult-site disease [32, 33, 34]. However, histological clearance is only obtained in 65–90% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some case reports (no RCTs) have claimed positive responses to topical IQ 5% in large superfi cial BCCs (Shumack et al 2004;Micali et al 2005) and multiple BCCs as observed in Gorlin syndrome (Kagy and Amonette 2000;Micali, Lacarrubba, et al 2003).…”
Section: Basal Cell Carcinomamentioning
confidence: 99%